2001
DOI: 10.1001/archinte.161.4.572
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Index and Serum High-Density Lipoprotein Cholesterol Concentration Among US Adults

Abstract: These findings from a nationally representative sample of US adults suggest that high dietary glycemic index and high glycemic load are associated with a lower concentration of plasma HDL-C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
155
3
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(181 citation statements)
references
References 19 publications
21
155
3
2
Order By: Relevance
“…Studies have demonstrated an association between quality as well as quantity of dietary carbohydrates in Europeans (Ford and Liu, 2001;Liu et al, 2001) and one in an Asian (Japanese) population (Amano et al, 2004;Murakami et al, 2006). This study differs from the earlier studies in that it was done in Asian Indians who are at much higher risk of premature CAD (McKeigue, 1992;Reddy and Yusuf, 1998).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Studies have demonstrated an association between quality as well as quantity of dietary carbohydrates in Europeans (Ford and Liu, 2001;Liu et al, 2001) and one in an Asian (Japanese) population (Amano et al, 2004;Murakami et al, 2006). This study differs from the earlier studies in that it was done in Asian Indians who are at much higher risk of premature CAD (McKeigue, 1992;Reddy and Yusuf, 1998).…”
Section: Discussionmentioning
confidence: 63%
“…Studies have shown that an increased intake of carbohydrates can lower serum HDL-C concentrations (Mancini et al, 1973;Yagalla et al, 1996;Anwar et al, 2007). In addition to the quantitative relationship between carbohydrate intake and HDL-C concentration, recent studies suggest that glycemic load, which depends on both the quality as well as the amount of dietary carbohydrates, may also influence HDL-C concentrations (Ford and Liu, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…So, dietary GL would be a stronger predictor of CVD risk factor than carbohydrate intake. Other researches have examined the correlations between dietary GI or GL and risk factors adjusting further confounding factors such as smoking status and alcohol consumption (Frost et al, 1999;Buyken et al, 2001;Ford & Liu, 2001;Liu et al, 2001). In the current study, after adjusting for smoking status (number of cigarettes per day) and alcohol consumption (g/week) in addition to total energy intake, dietary fiber intake, age, and exercise time, Body weight (kg) 60.3 (56.7, 63.9) 63.5 (60.1, 66.9) 65.8 (59.7, 71.8) 0.403 60.0 (56.0, 64.0) 61.9 (58.4, 65.4) 67.6 (62.3, 72.9) 0.068 BMI (kg/m 2 ) 25.2 (23.8, 26.6) 26.3 (25.1, 27.4) 26.9 (25.0, 28.8) 0.237 25.2 (23.7, 26.7) 25.5 (24.4, 26.6) 27.6 (26.0, 29.3) there were still significant correlations between dietary GI and HDL-c (P ¼ 0.011), TG (P ¼ 0.045), and IRI (P ¼ 0.021) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Higher dietary GI or GL was significantly associated with the incidence of diabetes (Salmeron et al, 1997a, b) and coronary heart disease (CHD) (Liu et al, 2000). Furthermore, an association between higher dietary GI or GL and risk factors of cardiovascular disease (CVD) such as lower HDLcholesterol (Frost et al, 1999;Ford & Liu, 2001;Liu et al, 2001), higher triacylglycerol (Wolever et al, 1995;Liu et al, 2001) and higher HbA 1c (Wolever et al, 1995;Buyken et al, 2001) as observed. These findings suggested the possible benefits that low GI or GL diet might have in the prevention and management of lifestyle-related disease such as diabetes and CVD.…”
Section: Introductionmentioning
confidence: 96%
“…Lowering the dietary GI by at least 12 points reduced triglycerides by approximately 9% in 10 out of 11 studies (Brand Miller, 1994) and recent data showed that a high carbohydrate diet made of low-GI foods significantly increased HDL levels by 5.4% compared to an isocaloric high carbohydrate=high GI diet (Luscombe et al, 1999). In addition, cross-sectional data (Frost et al, 1999;Ford & Liu, 2001) showed that dietary GI was inversely related to HDL cholesterol levels, which in turn were inversely related to triglycerides, and that GI was a stronger predictor of serum HDL levels than dietary fat (Frost et al, 1999). Other investigators have shown that the unwanted HDL reductions seen with some high carbohydrate diets may be transient (Heilbronn et al, 1999).…”
Section: The Glycemic Index In Coronary Heart Diseasementioning
confidence: 98%